Exploring the Impact of Human Rights on Diplomatic Relations: A Comparative Analysis of State Interactions - Naeli Fitria (Publikasi Indonesia, 2023)
Recent developments in the field of human rights have led to a renewed interest in promoting human rights internationally. Human rights issues emerge as an undeniable part of international negotiation or diplomacy in practice. Echoing human rights is an integral part of international relations since it helps states seek their national interests and improve the national condition of human rights. Moreover, it is arguably true that human rights diplomacy triggered states to build cooperation. One of the examples is South Africa during the Apartheid regime, which had the poorest record in fulfilling human rights due to human rights violations in terms of discrimination that resulted in conflict among civilians. With approximately more than 10,000 people killed during the liberation from 1985 to 1995, It has become an interesting case since it has been shown that human rights issues played a significant role in South Africa’s diplomatic relations during and post-Apartheid. This regime has transformed South Africa from an underdeveloped country to one of the most prosperous countries to date. This paper will discuss the relationships and influence between human rights and diplomacy. This paper sought the date through literature review research. Our analysis indicates that in struggling for freedom from the Apartheid regime, South Africa transformed its government system from an oppressive one to one of democracy. It has shown that the importance of human rights has revived the spirit of the national movement. In addition, the US initiated for the first time the establishment of the American Committee on South Africa to help with the liberation.